Scattering of acoustic waves on free surface perturbations in an elastic half-space - Franciszek WITOS (Archives of Acoustics)
This paper considers a semi-infinite, homogeneous and linearly elastic medium with a perturbed free surface. The perturbation is material loss. Using the Green function method, the first Born aproximation is found for the field of displacements dependent harmonically on time and subsequently energy relations for solutions obtained are calculated. The character and magnitude of scattering on the perturbation are thus defined for any mode occurring in a semi-infinite, homogeneous and linearly elastic medium. In addition, the case of perturbation described by periodic functions, which is essential in practice, is analyzed.